1994
DOI: 10.1159/000177831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil Treatment on Gentamicin Nephrotoxicity in Rats

Abstract: The effect of fish oil on gentamicin-induced nephrotoxicity was investigated in rats. Gentamicin (80 mg/kg/day intramuscularly for 6 days) produced the typical pattern of nephrotoxicity as shown by increases in serum creatinine and urea concentrations, and urinary N-acetyl-β-D-glucosaminidase (NAG) activity and proximal renal tubular necrosis. Fish oil (5.0 ml/kg/kday per os for 10 days) partially protected against the nephrotoxicity induced by gentamicin administered during the last 6 days of treatment with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Recently, dietary FO has been shown to protect against acetaminophen (paracetamol)induced hepatotoxicity (Speck and Lauterburgh 1991), ethanol-induced gastric mucosal injury in rats (Leung 1992), and a number of inflammatory diseases such as lupus nephritis (Chandrasekar and Fernandes 1994). Preliminary reports also showed partial protection by dietary FO x-3 fatty acids against cyclosporine/GMinduced nephrotoxicity (Thakkar et al 2000;Ali and Bashir 1994); however, the mechanism involved was not studied in detail. Our results thus support the rationale that x-3 fatty acids enriched FO may be an effective dietary supplementation in the management of cisplatin nephrotoxicity and other pathologies in which antioxidant defense mechanisms are impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dietary FO has been shown to protect against acetaminophen (paracetamol)induced hepatotoxicity (Speck and Lauterburgh 1991), ethanol-induced gastric mucosal injury in rats (Leung 1992), and a number of inflammatory diseases such as lupus nephritis (Chandrasekar and Fernandes 1994). Preliminary reports also showed partial protection by dietary FO x-3 fatty acids against cyclosporine/GMinduced nephrotoxicity (Thakkar et al 2000;Ali and Bashir 1994); however, the mechanism involved was not studied in detail. Our results thus support the rationale that x-3 fatty acids enriched FO may be an effective dietary supplementation in the management of cisplatin nephrotoxicity and other pathologies in which antioxidant defense mechanisms are impaired.…”
Section: Discussionmentioning
confidence: 99%
“…resulting in swelling, vacuolization and necrosis of epithelial cells, and accumulation of myelin-like bodies. 39 Furthermore, results of many studies have shown that altered concentrations of various biochemical indicators of oxidative stress in kidney tissue are due to GEN. 40 Because of the obvious responsibility of ROS in GENinduced renal damage, several antioxidant agents have been used to prevent GEN nephrotoxicity. 41 MK, a selective reversible cys-leukotriene-1 receptor (LTD4 receptor) antagonist, is used in the treatment of asthma and is reported to reduce airway eosinophilic inflammation in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…GEN is a widely used aminoglycoside antibiotic and has been shown to cause marked histological damage in particular to renal proximal convoluted tubules, 30,31 resulting in swelling, vacuolization, and necrosis of epithelial cells and accumulation of myelin-like bodies. 32 Furthermore, the results of many studies have shown that altered concentrations of various biochemical indicators of oxidative stress in kidney tissue are due to GEN. 33 Because of the obvious responsibility of ROS in GEN-induced renal damage, several antioxidant agents have been used to prevent GEN nephrotoxicity. 34 PE is rich in antioxidants of the polyphenolic class, which includes tannins and anthocyanins.…”
Section: Discussionmentioning
confidence: 99%